Human infection with dirofilarial repens in Malaysia - Shekhar, K.C.; Pathmanathan, R.; Krishnan, R. (Faculty of Medicine, University of Malaya, 1996)
Human dirofilariasis is a rare infection in Malaysia. Thus far, only two human cases have been reported viz. Dirofilaria immitis and D. (Nochtiella) repens and in both instances, adult worms were recovered from infected patients. The two cases reported in the present study, one from Melaka and the other from Penang, were diagnosed histologically. Based on the diagnostic criteria for identifying Dirofilaria in tissue sections, the parasites were identified as D. (Nochtiella) repens.